Myeloid Leukemias and Virally Induced Lymphomas in Miniature Inbred Swine: Development of a Large Animal Tumor Model - Duran-Struuck, Raimon; Matar, Abraham J.; Huang, Christene A. (Frontiers in Genetics, 2015)
The lack of a large animal transplantable tumor model has limited the study of novel therapeutic strategies for the treatment of liquid cancers. Swine as a species provide a natural option based on their similarities with humans and their already extensive use in biomedical research. Specifically, the MGH miniature swine herd retains unique genetic characteristics that facilitate the study of hematopoietic cell and solid organ transplantation. Spontaneously arising liquid cancers in these swine, specifically myeloid leukemias and B cell lymphomas, closely resemble human malignancies. The ability to establish aggressive tumor cell lines in vitro from these naturally occurring malignancies makes a transplantable tumor model a close reality. Here, we discuss our experience with myeloid and lymphoid tumors in MHC characterized miniature swine and future approaches regarding the development of a large animal transplantable tumor model.